Extracts from St. Mary's County, Maryland Death Certificates and Birth Certificates (that show stillborn children) from the Maryland State Archives, Annapolis, Maryland 1915-1920 (755 White Individuals) - Long, Charles David, transcribed and Compiled by
Extracts from Death Certificates and Birth Certificates from the Maryland Archives for St. Mary's County 1915 thru 1920